1990
DOI: 10.1002/cyto.990110610
|View full text |Cite
|
Sign up to set email alerts
|

Two‐color flow cytometric analysis of the expression of MAC and MHC Class II antigens on macrophages during tumor growth

Abstract: Tumor-bearing host (TBH) macrophages (M+) exhibit immune dysfunction that is concomitant with phenotypic changes. We examined M+ subpopulations by changes in the expression of surface antigens Mac-1, -2, -3, and Ia on normal and TBH peritoneal and splenic M+. M+ were double-labeled and analyzed by flow cytometry to observe multiple expression of surface antigens. Tumor growth alters the multiple expression of these M+ markers. Peritoneal and splenic M+ had different Mac+ and Mac+Ia+ population percentages. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Spleens normally have high numbers of class II ϩ Ms, which produce far less TNF-␣ and PGE 2 [118,119], and perhaps NO, than do class II Ϫ Ms. As expected, splenic Ms are much better antigen-presenting cells than are peritoneal Ms because splenic Ms express more MHC class II molecules [3,137,154,196]. Antigen presentation is drastically compromised in the TBH spleen because of increased numbers and suppressor activity of class II Ϫ Ms [3,137,156].…”
Section: Tumor Growth Alters Cell-surface Marker Expressionmentioning
confidence: 75%
See 4 more Smart Citations
“…Spleens normally have high numbers of class II ϩ Ms, which produce far less TNF-␣ and PGE 2 [118,119], and perhaps NO, than do class II Ϫ Ms. As expected, splenic Ms are much better antigen-presenting cells than are peritoneal Ms because splenic Ms express more MHC class II molecules [3,137,154,196]. Antigen presentation is drastically compromised in the TBH spleen because of increased numbers and suppressor activity of class II Ϫ Ms [3,137,156].…”
Section: Tumor Growth Alters Cell-surface Marker Expressionmentioning
confidence: 75%
“…In addition, tumors can affect changes in M phenotype and thus favor a particular function. Using depletion [12,136,192,193] and single [154,[193][194][195] and double-label [195,196] fluorescent antibody studies, we showed a shift in M subpopulations, changes in M marker expression, and changes in M function during tumor growth.…”
Section: Tumor Growth Leads To Shifts In M Subpopulationsmentioning
confidence: 99%
See 3 more Smart Citations